Prevalence of hypertension and cardiovascular risk in patients with gastrointestinal angiodysplasia: the role of aortic stiffness and non-dipper blood pressure patterns; predictive value of novel inflammatory biomarkers - Abdulkadir Çakmak; Ömer Kertmen; Şirin Çetin (Frontiers in Cardiovascular Medicine)
Gastrointestinal angiodysplasia (GIAD) is the most prevalent vascular malformation of the gastrointestinal (GI) tract, primarily affecting elderly individuals, with the colon being the most common site of involvement. Patients with GIAD often present with cardiovascular comorbidities such as hypertension, increased aortic stiffness, and left ventricular hypertrophy (LVH). This study aimed to evaluate the prevalence of hypertension and its association with aortic stiffness in patients diagnosed with GIAD with particular attention to the role of non-dipper blood pressure patterns. Additionally, the predictive value of inflammatory biomarkers—including the C-reactive protein to albumin ratio (CAR), blood urea nitrogen to albumin ratio (BAR), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-C-reactive protein ratio (LCR), and systemic immune response index (SIRI) was investigated concerning vascular risk and disease pathophysiology. A total of 25 patients with GIAD and 25 matched controls were included. All participants underwent comprehensive cardiovascular evaluation, including physical examination, electrocardiography, transthoracic echocardiography, and 24 h ambulatory blood pressure monitoring (ABPM). Demographic characteristics, biochemical parameters, echocardiographic indices, and ABPM findings were analyzed. Receiver operating characteristic (ROC) curve analysis, area under curve (AUC) and multivariate regression models were used to assess the predictive value of inflammatory biomarkers. GIADs were predominantly localized in the colon (40%). Compared to controls, patients exhibited significantly increased aortic stiffness, greater aortic systolic and diastolic diameters, and a higher prevalence of LVH. The non-dipper blood pressure pattern was notably more frequent among patients (84% vs. 4%, p < 0.0001). Serum creatinine and potassium levels were significantly elevated in the patient group. Among inflammatory biomarkers, CAR (AUC: 0.70), BAR (AUC: 0.81), and NLR (AUC: 0.69) demonstrated the strongest associations with GIAD, with elevated CAR and BAR levels increasing disease risk by 4- to 6-fold. This study underscores the significant cardiovascular burden in patients with GIAD, characterized by hypertension, increased aortic stiffness, LVH, and a high prevalence of non-dipper blood pressure patterns. The integration of inflammatory biomarkers such as CAR and BAR may enhance early diagnosis and facilitate personalized management strategies. However, the limited sample size, single-center design and focus on only specific markers in our study may limit the generalizability of the results.